Inverse perovskite solar cell and buried bottom interface adjusting method thereof
By preparing a hybrid HTL layer in an inverse perovskite solar cell, and mixing PA with 2PACz molecules to form a Co-SAM layer, the problem of incomplete coverage of the SAM layer is solved, and the photoelectric conversion efficiency and stability of the battery are significantly improved.
Patent Information
- Application Number
- CN202411903459.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-23
AI Technical Summary
In existing inverse perovskite solar cells, the SAM layer is incompletely covered, and there are many defects and holes, resulting in interfacial carrier recombination problems and affecting the photoelectric conversion efficiency and stability of the battery.
By preparing a mixed HTL layer on the surface of the ITO film, mixing PA molecules with 2PACz molecules to form a more uniform and dense Co-SAM layer, adjusting the energy level of the SAM layer to match the energy level between the perovskite layer and promoting carrier transmission.
The photoelectric conversion efficiency and long-term stability of inverse perovskite solar cells are significantly improved, the uniformity and density of the SAM layer are ensured, and the interfacial carrier recombination problem is reduced.
Smart Images

Figure CN119698206A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to an inverted perovskite solar cell and a method for adjusting a buried interface thereof. Background Art
[0002] Perovskite solar cells (PSCs) with an inversion (pin) structure are considered to be one of the mainstream technological routes for the commercialization of perovskite photovoltaic technology due to their competitive power conversion efficiency (PCE), good stability, and compatibility with stacked solar cells.
[0003] Currently, the PCE of inversion perovskite solar cells exceeds 26.7% due to the development of hole transport layers (HTLs) and passivation strategies. In particular, self-assembled molecules (SAMs)-based HTLs are widely used in high-efficiency inversion perovskite solar cells due to their advantages of efficient hole extraction and low non-radiative recombination losses. Although SAMs have the potential to achieve high optoelectronic performance perovskite solar cells, it is still challenging to achieve high-density, tightly packed SAMs. For example, the inherent amphiphilic properties of SAMs often lead to undesirable self-aggregation, especially in alcohol solvents, inducing the formation of SAMs micelles. When SAM molecules bind to the substrate surface, an additional energy barrier may be required during the dispersion of micelles. Therefore, dense and compact SAM structures cannot be easily and stably obtained. In addition, due to the rough substrate and solution deposition method, defects in the monolayer are inevitable, especially for those areas lacking SAM coverage. These defects may cause current leakage at the buried interface, resulting in energy loss and instability of optoelectronic devices.
[0004] To address this problem, many strategies have been studied, such as optimizing the SAM layer deposition technology, realizing a double-layer structure, and adding additives. For example, evaporating Me-4PACz to prepare the HTL layer enhances the wettability of the perovskite and changes the morphology of the perovskite without significantly affecting its chemical properties. This method effectively improves the interface quality between the HTL and the perovskite, helping to form a lossless contact. The double-layer structure combining NiOx and SAM shows promise in reducing interface losses and increasing surface coverage, resulting in enhanced device stability.
[0005] In addition, the use of small molecules, such as methylphosphonic acid (MPA) and 3-mercaptopropionic acid (3-MPA), can reduce the interfacial energy loss of SAM / perovskite and reduce the aggregation of SAM. These methods are mainly used to increase the surface coverage, adjust the energy level, and reduce the energy dissipation at the perovskite / SAM. Although these buried interface modification strategies have made good progress in improving the performance of perovskite solar cells, it is still difficult to strike a balance between performance and stability, so it is still challenging to obtain a uniform, dense and stable SAM layer. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide an inverted perovskite solar cell and a buried interface adjustment method thereof in view of the deficiencies in the above-mentioned prior art, so as to solve the technical problems of incomplete SAM layer coverage, the presence of many defects and holes, and interface carrier recombination, and to provide a simple and effective strategy to adjust the SAM distribution and improve the stability of the SAM film.
[0007] The present invention adopts the following technical solutions: A method for adjusting the buried interface of an inversion perovskite solar cell comprises the following steps: Prepare a hybrid HTL layer on the surface of the ITO film; FAPbI3, MAPbBr3 and CsI were prepared according to (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 in a mixed solvent containing N, N-dimethylformamide and dimethyl sulfoxide in a stoichiometric ratio, and stirred at room temperature overnight under a nitrogen atmosphere to prepare a perovskite precursor solution, and the prepared perovskite precursor solution was placed on a FTO / Co-SAM substrate for spin coating, and chlorobenzene was added dropwise as an anti-solvent before the spin coating process was completed. After the spin coating was completed, the perovskite precursor film was heated to obtain a dark film with a mirror image, thereby obtaining a perovskite light-absorbing layer; A C60 layer, a BCP layer and a Ag electrode are sequentially prepared on the prepared perovskite light-absorbing layer.
[0008] Preferably, the preparation of the hybrid HTL layer is specifically as follows: 2PACz and PA molecules were mixed in an ethanol solvent at a molar ratio of (4-9):1 to prepare a 0.4-1.0 mg / mL mixed SAM solution, which was stirred at room temperature overnight. The mixed SAM solution was then dropped onto the ITO film for spin coating and heating.
[0009] Preferably, the spin coating process is performed for 30 to 40 seconds at a rotation speed of 2000 to 3000 rpm, and then heated at 90 to 110° C. for 8 to 15 minutes.
[0010] Preferably, the molar concentrations of FAPbI3, MAPbBr3 and CsI are all 1.4~1.6 M, and 2 mol%~9 mol% of PbI2 and 10 mol%~30 mol% of MACl are additionally added.
[0011] Preferably, in the mixed solvent, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is (3-4):1.
[0012] Preferably, the spin coating process is performed for 40 to 50 seconds at a rotation speed of 4000 to 5000 rpm, and then heated at 100 to 120° C. for 30 to 60 minutes.
[0013] Preferably, after the spin coating is completed, the perovskite precursor film is heated at 100-120° C. for 30-60 min to obtain a perovskite light absorbing layer.
[0014] Preferably, the thickness of the C60 layer is 30-40 nm. -3 ~10 -4 Pa vacuum at a rate of 0.2~0.4 Å / s; the thickness of the BCP layer is 4~10 nm. -3 ~10 -4 Pa vacuum at a rate of 0.1~0.15 Å / s; the thickness of the Ag electrode is 90~110 nm. -3 ~10 -4 It is made by evaporation at a rate of 1.0~2.0 Å / s under a vacuum degree of PaPa.
[0015] Another technical solution of the present invention is an inversion perovskite solar cell.
[0016] Preferably, the open circuit voltage is 1.175-1.187 V; the current density is 25.65-25.92 mA / cm 2 ; The fill factor is 83.74%~85.01%; the battery efficiency is 25.55%~25.73%; after storage for 1000 h, the photoelectric conversion efficiency becomes 92%~93.5% of the initial value.
[0017] Compared with the prior art, the present invention has at least the following beneficial effects: A method for adjusting the buried interface of an inverted perovskite solar cell introduces a mixed SAM transport layer between the perovskite layer and ITO. Due to the spatial repulsion of PA molecules, the SAM shows a more uniform and dense distribution on the ITO electrode, and the energy level of the SAM layer is adjusted to make it more matched with the energy level of the perovskite layer, thereby promoting carrier transport. Finally, the mixed SAM layer forms a stable hole transport layer at the buried interface of the inverted perovskite solar cell, significantly improving the photoelectric conversion efficiency and long-term stability of the inverted perovskite solar cell; it can effectively seal the battery film layer and isolate it from the external air environment, so that the air and moisture in the external environment cannot enter between the substrate and the glass plate and affect the battery film layer, thereby avoiding the decomposition of the functional materials of the battery and affecting the battery performance, so that the battery can be used stably for a long time.
[0018] Furthermore, 2PACz and PA molecules were mixed in an ethanol solvent or an isopropanol solvent at a molar ratio of (3~9):1 to prepare a 0.4~1.0 mg / mL mixed SAM solution, which was stirred at room temperature overnight. The mixed SAM solution was then dropped onto the ITO film for spin coating and heating to obtain a SAM solution with better dispersion.
[0019] Furthermore, the spin coating process was performed for 30 to 40 s at a rotation speed of 2000 to 3000 rpm, and then heated at 90 to 110 °C for 8 to 15 min to obtain a more uniform and dense hole transport layer film.
[0020] Furthermore, the molar concentrations of FAPbI3, MAPbBr3, and CsI were all 1.3–1.6 M, and 2–9 mol% of PbI2 and 10–30 mol% of MACl were additionally added to obtain an efficient perovskite precursor solution formulation.
[0021] Furthermore, in the mixed solvent, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 3:1-4:1, thereby obtaining a uniformly dispersed perovskite precursor solution.
[0022] Furthermore, the spin coating process was performed for 40 to 50 s at a rotation speed of 4000 to 5000 rpm, and then heated at 100 to 120 °C for 30 to 60 min to obtain a smooth and uniform perovskite film.
[0023] Furthermore, the thickness of the C60 layer is 30~40 nm. -3 ~10 -4 Pa vacuum at a rate of 0.2~0.4 Å / s; the thickness of the BCP layer is 4~10 nm. -3 ~10 -4Pa vacuum at a rate of 0.1~0.15 Å / s; the thickness of the Ag electrode is 90~110 nm. -3 ~10 -4 It is made by evaporation at a rate of 1.0~2.0 Å / s under a vacuum degree of 1.0 Pa. A uniform and dense electron transport layer, hole blocking layer and electrode are obtained.
[0024] In summary, the present invention can prepare a more uniform and dense SAM layer, significantly improve the hole transport performance of the perovskite and HTL interface, and improve the photoelectric performance and long-term stability of perovskite solar cells.
[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings to be used in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 It is a schematic diagram of the structure of 2PACz molecule and PA molecule in the present invention; Figure 2 Schematic diagram of the device structure of the inverted perovskite solar cell in the present invention; Figure 3 Energy dispersion spectra (EDS) of P of the 2PACz film and the 2PACz+PA film of the present invention; Figure 4 The device current-voltage curve (JV) based on 2PACz substrate and 2PACz+PA substrate in the present invention; Figure 5 It is the maximum power point tracking curve (MPP) of the packaged device based on 2PACz substrate and 2PACz+PA substrate in the present invention under 65° C. in ambient air. DETAILED DESCRIPTION
[0028] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0030] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0031] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0032] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0033] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6-22" means that all real numbers between "6-22" have been listed in this document, and "6-22" is just an abbreviation of these numerical combinations.
[0034] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0035] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0036] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0037] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0038] The present invention provides a method for adjusting the buried interface of an inverted perovskite solar cell. A mixed SAM layer (Co-SAM) is prepared by introducing a small molecule 4,4,4-phosphoryltribenzoic acid (PA) into [2-(9H-carbazole-9-yl)ethyl]phosphoric acid (2PACz). Due to the spatial repulsion of the PA molecules, the SAMs show a more uniform and dense distribution on the ITO electrode. In addition, the PA-modified SAMs have a smoother surface morphology, improve the crystallization of the perovskite layer, and finally achieve stronger hole transport performance and better interface stability in the inverted perovskite solar cell device.
[0039] The present invention provides a method for adjusting the buried interface of an inverse perovskite solar cell, comprising the following steps: S1, treating the ITO film; Use detergent, deionized water, ethanol, acetone and deionized water for continuous ultrasonic cleaning for 15-20 min respectively.
[0040] S2, preparing a hybrid hole transport layer (HTL layer); 2PACz and PA molecules were mixed in an ethanol solvent at a molar ratio of (3-9):1 to prepare a 0.4-1.0 mg / mL mixed SAM solution, which was stirred at room temperature overnight. 80-150 μL of the solution was dripped onto a 2.5 cm×2.5 cm ITO surface and spin-coated for 30-40 s at a speed of 2000-3000 rpm using a gel coater. The surface was then heated at 90-110 °C on a heating table for 8-15 min.
[0041] S3, preparation of perovskite light absorbing layer; FAPbI3 with a molar concentration of 1.4 ~ 1.6 M, MAPbBr3 with a molar concentration of 1.4 ~ 1.6 M, and CsI with a molar concentration of 1.4 ~ 1.6 M were prepared according to (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 was dissolved in 1.0 mL of a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a stoichiometric ratio, wherein the volume ratio of DMF to DMSO was (3-4):1. The perovskite precursor solution was prepared by stirring at room temperature overnight under a nitrogen atmosphere (glove box). 80 μL-180 μL of the prepared perovskite precursor solution was measured with a pipette and placed on a FTO / Co-SAM substrate. The control program of the coater was adjusted to 4000-5000 rpm and spin-coated for 40-50 s. A certain amount of chlorobenzene was added as an anti-solvent 7-10 s before the end of the spin-coating process. After the spin-coating was completed, the perovskite precursor film was placed on a heating plate and heated at 100-120 °C for 30-60 min to obtain a dark film with a mirror image.
[0042] Preparation of S4 and C60 layers; In 10 -3 ~10 -4 A 30~40 nm C60 film was evaporated at a rate of 0.2~0.4 Å / s under a vacuum degree of 1.3 Pa.
[0043] S5, preparation of hole blocking layer BCP film; In 10 -3 ~10 -4 A 4~10 nm BCP film was evaporated at a rate of 0.1~0.15 Å / s under a vacuum degree of 1.3 Pa.
[0044] S6. Preparation of Ag electrode.
[0045] In 10 -3 ~10 -4 A 90~110 nm Ag electrode was evaporated at a rate of 1.0~2.0 Å / s under a vacuum degree of 1.0~2.0 Å / s.
[0046] The Co-SAM layer prepared by the method of the present invention has a higher P element content, is denser and more uniform than the 2PACz-SAM layer; The inverted perovskite solar cell based on the Co-SAM layer prepared by the present invention significantly improves the photovoltaic performance, and the improved photovoltaic parameters are: Open circuit voltage 1.175~1.187 V; Current density 25.65~25.92 mA / cm 2 ; Fill factor 83.74%~85.01%; Battery efficiency is 25.55%~25.73%.
[0047] The photovoltaic parameters of the inverse perovskite solar cell based on the 2PACz-SAM layer are: Open circuit voltage 1.142~1.155 V; Current density 25.12~25.58 mA / cm 2 ; The filling factor is 79.61%~81.69%; The battery efficiency is 22.97%~23.84%.
[0048] The inverse perovskite solar cell based on the Co-SAM layer prepared by the present invention was packaged and then subjected to an MPP aging test in an aging box in ambient air, 50-65°C, 45% RH~65% RH, and under standard sunlight. After storage for 1000 h, the photoelectric conversion efficiency became 92%~93.1% of the initial value.
[0049] The photoelectric conversion efficiency of the inverted perovskite solar cell prepared based on the 2PACz-SAM layer becomes 75.6% to 77.9% of the initial value after being stored in an aging box under standard sunlight in ambient air, 50 to 65°C, 45% to 65% RH for 1000 hours. Therefore, the present invention significantly improves the photoelectric performance and stability of the inverted perovskite solar cell.
[0050] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0051] In the following examples and comparative examples, EDS tests were obtained using Xplore 30 from OXFORD INSTRUMENTS, UK, at an accelerating voltage of 15 kV; The test method for photoelectric conversion efficiency is: The JV test was performed using an electrochemical workstation (CHI660E, China) and a solar simulator (Newport, 94063A, USA). The solar simulator used a KG-5 Si diode to calibrate the light intensity to a standard sunlight (AM 1.5G spectrum, light intensity 100 mW / cm 2 ); The MPP test was conducted using the Solar Cell Burn-in System (SCS600 series) from ZOLIX INSTRUMENTS CO, LTD of China; Device packaging method: To encapsulate the device, multi-layer thin film encapsulation (MFE) technology is used. This encapsulation technology is achieved through ultra-thin inorganic-organic-inorganic laminate films, which not only provides more effective protection against water and oxygen attack (from outside to inside), but also prevents leakage of components (from inside to outside).
[0052] On the prepared device, plasma enhanced chemical vapor deposition (PECVD) was used to prepare Si3N4 of about 10 μm, then inkjet printing was used to prepare acrylate of about 1 mm, and finally PECVD was used to prepare Si3N4 of about 10 μm to complete the encapsulation.
[0053] Example 1 S1: Treatment of ITO: ultrasonic cleaning with detergent, deionized water, ethanol, acetone and deionized water for 20 min each; S2: Preparation of hybrid HTL layer: 2PACz and PA molecules were mixed in an ethanol solvent at a molar ratio of 9:1 to prepare a 1.0 mg / mL SAM solution, and stirred at room temperature overnight. 150 μL of the solution was pipetted and dropped onto a 2.5 cm×2.5 cm ITO surface, and spin-coated for 40 s at a speed of 3000 rpm using a gel coater, and then heated on a heating table at 110 °C for 15 min.
[0054] S3, preparation of perovskite light absorbing layer: 1.6 M FAPbI3, 1.6 M MAPbBr3 and 1.6 M CsI were prepared according to (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 was dissolved in 1.0 mL of a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a stoichiometric ratio, wherein the volume ratio of DMF to DMSO was 3:1. The perovskite precursor solution was prepared by stirring at room temperature overnight under a nitrogen atmosphere (glove box). 80 μL of the prepared perovskite precursor solution was measured with a pipette and placed on the FTO / Co-SAM substrate. The control program of the coater was adjusted to 4000 rpm and the spin coating was performed for 50 s. A certain amount of chlorobenzene was added as an anti-solvent at the 7th second before the end of the spin coating process. After the spin coating was completed, the perovskite precursor film was placed on a heating plate and heated at 110°C for 50 min to obtain a dark film with a mirror image. Preparation of S4 and C60 layers: -4 A 40 nm C60 film was evaporated at a rate of 0.2 Å / s under a vacuum degree of 1.3 Pa; S5. Preparation of BCP layer: -4 A 5 nm BCP film was evaporated at a rate of 0.1 Å / s under a vacuum degree of 1.3 Pa; S6. Preparation of Ag electrode: -4 A 100 nm Ag electrode was evaporated at a rate of 1.5 Å / s under a vacuum degree of 1.0 Pa.
[0055] Comparative Example 1 The HTL layer of Example 1 was prepared into a Co-SAM layer using a mixed solution of 0.5 mg / mL 2PACz and PA molecules (molar ratio of 4:1).
[0056] Comparative Example 2 The HTL layer of Example 1 was prepared into a SAM layer using a 0.5 mg / mL 2PACz solution.
[0057] Experimental Example 1 The Co-SAM layer of Comparative Example 1 and the 2PACz-SAM layer of Comparative Example 2 in Example 1 were subjected to EDS testing to obtain P element energy dispersion spectra of the Co-SAM layer and the 2PACz-SAM layer. The P element content of the Co-SAM layer of Comparative Example 1 was higher than that of the 2PACz-SAM layer of Comparative Example 2, and the P element distribution of the Co-SAM layer of Comparative Example 1 was more uniform and dense than that of the 2PACz-SAM layer of Comparative Example 2. The results are as follows: Figure 3 shown.
[0058] Example 2 S1. Treatment of ITO: ultrasonic cleaning with detergent, deionized water, ethanol, acetone and deionized water for 15 min each; S2. Preparation of mixed HTL layer: 2PACz and PA molecules were mixed in an ethanol solvent at a molar ratio of 3:1 to prepare a mixed SAM solution of 0.4 mg / mL, and stirred at room temperature overnight. 80 μL of the solution was added dropwise onto a 2.5 cm×2.5 cm ITO surface, and spin-coated for 30 s at a speed of 2000 rpm using a gel coater, and then heated on a heating table at 90 °C for 8 min. S3, preparation of perovskite light absorbing layer: 1.4 M FAPbI3, 1.4 M MAPbBr3 and 1.4 M CsI were prepared according to (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 was dissolved in 1.0 mL of a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a stoichiometric ratio, wherein the volume ratio of DMF to DMSO was 4:1. The perovskite precursor solution was prepared by stirring at room temperature overnight under a nitrogen atmosphere (glove box). 180 μL of the prepared perovskite precursor solution was measured with a pipette and placed on the FTO / Co-SAM substrate. The control program of the coater was adjusted to 5000 rpm and the spin coating was performed for 40 s. A certain amount of chlorobenzene was added as an anti-solvent at the 10th s before the end of the spin coating process. After the spin coating was completed, the perovskite precursor film was placed on a heating plate and heated at 120°C for 30 min to obtain a dark film with a mirror image. Preparation of S4 and C60 layers: -3 A 30 nm C60 film was evaporated at a rate of 0.4 Å / s under a vacuum degree of 1.3 Pa; S5. Preparation of BCP layer: -3 A 10 nm BCP film was evaporated at a rate of 0.15 Å / s under a vacuum degree of 1.3 Pa; S6. Preparation of Ag electrode:-3 A 90 nm Ag electrode was evaporated at a rate of 1.0 Å / s under a vacuum degree of 1.0 Pa.
[0059] Comparative Example 3 The Co-SAM layer of Example 2 is prepared as the HTL layer of an inverse perovskite solar cell.
[0060] Comparative Example 4 The 2PACz-SAM layer of Example 2 was prepared as the HTL layer of an inverse perovskite solar cell.
[0061] Experimental Example 2 The inverted perovskite solar cell based on the Co-SAM layer and the inverted perovskite solar cell based on the 2PACz-SAM layer of Comparative Example 3 in Example 2 were subjected to JV performance tests. The inverted perovskite solar cell based on the Co-SAM layer had better efficiency under standard simulated sunlight irradiation, and its photovoltaic parameters of reverse scanning were: open circuit voltage of 1.187 V, current density of 25.79 mA / cm 2 The fill factor is 84.05%, the cell efficiency is 25.73%, and the photovoltaic parameters of the inverse perovskite solar cell based on the 2PACz-SAM layer under standard simulated sunlight are: open circuit voltage is 1.155 V, current density is 25.58 mA / cm 2 , the fill factor is 80.69% and the cell efficiency is 23.84%. Figure 4 And as shown in Table 1.
[0062] Table 1
[0063] Example 3 S1. Treatment of ITO: ultrasonic cleaning with detergent, deionized water, ethanol, acetone and deionized water for 15 min each; S2. Preparation of mixed HTL layer: 2PACz and PA molecules were mixed in an ethanol solvent at a molar ratio of 4:1 to prepare a mixed SAM solution of 0.5 mg / mL, and stirred at room temperature overnight. 100 μL of the solution was added dropwise onto a 2.5 cm×2.5 cm ITO surface, and spin-coated for 30 s at a speed of 3000 rpm using a gel coater, and then heated on a heating table at 100 °C for 10 min. S3, preparation of perovskite light absorbing layer: 1.4 M FAPbI3, 1.4 M MAPbBr3 and 1.4 M CsI were prepared according to (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I0.95 Br 0.05 )3 was dissolved in 1.0 mL of a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a stoichiometric ratio, wherein the volume ratio of DMF to DMSO was 4:1. The perovskite precursor solution was prepared by stirring at room temperature overnight under a nitrogen atmosphere (glove box). 100 μL of the prepared perovskite precursor solution was measured with a pipette and placed on the FTO / Co-SAM substrate. The control program of the coater was adjusted to 4000 rpm and the spin coating was performed for 40 s. A certain amount of chlorobenzene was added as an anti-solvent at the 8th s before the end of the spin coating process. After the spin coating was completed, the perovskite precursor film was placed on a heating plate and heated at 100 °C for 60 min to obtain a dark film with a mirror image. Preparation of S4 and C60 layers: -3 A 30 nm C60 film was evaporated at a rate of 0.3 Å / s under a vacuum degree of 1.3 Pa; S5. Preparation of BCP layer: -3 A 4 nm BCP film was evaporated at a rate of 0.1 Å / s under a vacuum degree of 1.3 Pa; S6. Preparation of Ag electrode: -3 A 110 nm Ag electrode was evaporated at a rate of 2.0 Å / s under a vacuum degree of 1.3 Pa.
[0064] Experimental Example 3 The inverted perovskite solar cell prepared based on the Co-SAM layer and the inverted perovskite solar cell prepared based on the 2PACz-SAM layer in Example 3 were packaged and subjected to an MPP aging test in an aging box in ambient air, 65°C, 50% RH, and a standard sunlight. After testing, the photoelectric conversion efficiency of the inverted perovskite solar cell prepared based on the Co-SAM layer of the present invention after being stored in an aging box in ambient air, 65°C, 50% RH, and a standard sunlight for 1000 h became 93.1% of the initial value, while the photoelectric conversion efficiency of the inverted perovskite solar cell prepared based on the 2PACz-SAM layer after being stored in an aging box in ambient air, 65°C, 50% RH, and a standard sunlight for 1000 h became 77.9% of the initial value. The results are as follows: Figure 5 Therefore, the present invention significantly improves the service life and stability of the inverse perovskite solar cell.
[0065] In summary, the present invention provides an inverted perovskite solar cell and a buried interface adjustment method thereof, solves the problem of incomplete SAM layer coverage, the presence of many defects and holes through the buried interface technology, forms a stable hole transport layer at the buried interface of the inverted perovskite solar cell, avoids direct contact between the perovskite layer and the ITO layer, reduces the problem of interface carrier recombination, and thus ensures the high performance of the battery. The buried interface technology of the present invention has simple process, low material cost, is suitable for industrial application, and has broad application prospects.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for adjusting the buried interface of an inverse perovskite solar cell, characterized in that: The following steps are involved: Prepare a hybrid HTL layer on the surface of the ITO film; FAPbI3, MAPbBr3 and CsI were prepared according to (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 in a mixed solvent containing N, N-dimethylformamide and dimethyl sulfoxide in a stoichiometric ratio, and stirred at room temperature overnight under a nitrogen atmosphere to prepare a perovskite precursor solution, and the prepared perovskite precursor solution was placed on a FTO / Co-SAM substrate for spin coating, and chlorobenzene was added dropwise as an anti-solvent before the spin coating process was completed. After the spin coating was completed, the perovskite precursor film was heated to obtain a dark film with a mirror image, thereby obtaining a perovskite light-absorbing layer; A C60 layer, a BCP layer and a Ag electrode are sequentially prepared on the prepared perovskite light-absorbing layer.
2. The method for adjusting the buried interface of an inverse perovskite solar cell according to claim 1, characterized in that: The preparation of the hybrid HTL layer is specifically as follows: 2PACz and PA molecules were mixed in an ethanol solvent at a molar ratio of (4-9):1 to prepare a 0.4-1.0 mg / mL mixed SAM solution, which was stirred at room temperature overnight. The mixed SAM solution was then dropped onto the ITO film for spin coating and heating.
3. The method for adjusting the buried interface of an inverse perovskite solar cell according to claim 2, characterized in that: The spin coating time is 30~40 s, the rotation speed is 2000~3000 rpm, and then heated at 90~110 ℃ for 8~15 min.
4. The method for adjusting the buried interface of an inverse perovskite solar cell according to claim 1, characterized in that: The molar concentrations of FAPbI3, MAPbBr3, and CsI were all 1.4–1.6 M, with additional additions of 2 mol%–9 mol% PbI2 and 10 mol%–30 mol% MACl.
5. The method for adjusting the buried interface of an inverse perovskite solar cell according to claim 4, characterized in that: In the mixed solvent, the volume ratio of N,N-dimethylformamide and dimethyl sulfoxide is (3~4):
1.
6. The method for adjusting the buried interface of an inverse perovskite solar cell according to claim 1, characterized in that: The spin coating time is 40~50 s, the rotation speed is 4000~5000 rpm, and then heated at 100~120 ℃ for 30~60 min.
7. The method for adjusting the buried interface of an inverse perovskite solar cell according to claim 1, characterized in that: After the spin coating is completed, the perovskite precursor film is heated at 100~120 ℃ for 30~60 min to obtain the perovskite light-absorbing layer.
8. The method for adjusting the buried interface of an inverse perovskite solar cell according to claim 1, characterized in that: The thickness of the C60 layer is 30~40 nm. -3 ~10 -4 Pa vacuum at a rate of 0.2~0.4 Å / s; the thickness of the BCP layer is 4~10 nm. -3 ~10 -4 Pa vacuum at a rate of 0.1~0.15 Å / s; the thickness of the Ag electrode is 90~110 nm. -3 ~10 -4 It is made by evaporation at a rate of 1.0~2.0 Å / s under a vacuum degree of PaPa.
9. An inverse perovskite solar cell, characterized in that: The inverse perovskite solar cell is prepared according to the method for adjusting the buried interface of any one of claims 1 to 8.
10. The inverted perovskite solar cell according to claim 9, characterized in that: The open circuit voltage is 1.175~1.187 V; the current density is 25.65~25.92 mA / cm 2 ; The fill factor is 83.74%~85.01%; the battery efficiency is 25.55%~25.73%; after storage for 1000 h, the photoelectric conversion efficiency becomes 92%~93.5% of the initial value.
Citation Information
Patent Citations
Perovskite solar cell and preparation method thereof
CN116782675A
Application of 4, 4 ', 4' '-nitrotribenzoic acid in preparation of trans-perovskite solar cell and trans-perovskite solar cell
CN119173055A